Integration of mass drug administration programmes in Nigeria: the challenge of schistosomiasis - Richards Jr Frank O; Eigege Abel; Miri Emmanuel S; Jinadu MY; Hopkins Donald R (The World Health Organization, 2006)
PROBLEM: Annual mass drug administration (MDA) with safe oral anthelminthic drugs (praziquantel, ivermectin and albendazole) is the strategy for control of onchocerciasis, lymphatic filariasis (LF) and schistosomiasis. District health officers seek to integrate treatment activities in areas of overlapping disease endemicity, but they are faced with having to merge different programmatic guidelines. APPROACH: We proceeded through the three stages of integrated MDA implementation: mapping the distribution of the three diseases at district level; tailoring district training and logistics based on the results of the mapping exercises; and implementing community-based annual health education and mass treatment where appropriate. During the process we identified the "know-do" gaps in the MDA guidelines for each disease that prevented successful integration of these programmes. LOCAL SETTING: An integrated programme launched in 1999 in Plateau and Nasarawa States in central Nigeria, where all three diseases were known to occur. RELEVANT CHANGES: Current guidelines allowed onchocerciasis and LF activities to be integrated, resulting in rapid mapping throughout the two states, and states-wide provision of over 9.3 million combined ivermectin-albendazole treatments for the two diseases between 2000 and 2004. In contrast, schistosomiasis activities could not be effectively integrated because of the more restrictive guidelines, resulting in less than half of the two states being mapped, and delivery of only 701 419 praziquantel treatments for schistosomiasis since 1999. LESSONS LEARNED: Integration of schistosomiasis into other MDA programmes would be helped by amended guidelines leading to simpler mapping, more liberal use of praziquantel and the ability to administer praziquantel simultaneously with ivermectin and albendazole.